PF.09 Chromosomal Microarray (CMA) Use For the Prenatal Detection of Chromosome Anomalies: Model-Based Health Economic Evaluation. (26th April 2013) - Hillman, SC; Barton, PM; Roberts, TE; Maher, ER; Kilby, MD
Abstract : Chromosomal microarray (CMA) technology is increasingly used to detect chromosomal anomalies in the prenatal setting. Although its increased detection rates over karyotyping has been proven the cost-effectiveness is yet to be established. A decision tree was built and populated using two data sets; that of the literature from 21 journal articles and 13755 fetal samples where there was a range of indications for testing and data from 17 cohorts where the indication for testing was abnormalities on fetal ultrasound scan, 4276 fetal samples are included. Costs included were those incurred by the West Midlands Genetics laboratory. Staff costs were taken from Unit costs of health and social care 2011. When the base case cost of CMA is £405 and there is a range of indications for performing testing, CMA will cost an extra £6800 per case detected over karyotyping. CMA will cost an extra £2600 over karyotyping per case detected when the indication is abnormal ultrasound scan. Threshold analysis shows that when the cost of CMA is reduced to £220 it becomes the cost-effective option. Cost effectiveness association curves show that for any referral indication when the willingness to pay is >£7500 and for abnormal scans when the WTP is >2830 the probability of CMA being cost effective is over 95%. CMA will become the cost effective option of the future as technology costs fall. At the present time for abnormal ultrasound scan CMA may be considered if the WTP per case detected is £2600 in addition to standard costs.